The Significance of the Teacher’s Role in the Identification and Development of Giftedness in Students - Sekulić, Marija R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
At today’s level of social development, the prevailing understanding is that every child has the right to education in accordance with their needs and capabilities. Accordingly, the request for support that schools and education should provide for the development of gifted students, who are expected to be the future bearers of prosperity and development, is particularly emphasized. Since in teaching, especially at the younger school age, development has a global character, it is necessary, first of all, to provide certain conditions that have a stimulating effect on the overall development and that can be aimed at recognizing and developing potential giftedness. Acknowledging the fact that the overall school experience and the results of numerous researches support the prevailing belief that gifted students, or at least most of them remain in regular classes, in addition to the terminological and conceptual definition of giftedness and the characteristics of gifted students, the main attention in the work will be focused on the importance and role of teachers in identifying gifted students and working with them.